Acute Kidney Injury Secondary to Abdominal Tuberculosis: A Diagnostic Dilemma - A Case Report - Yadav, Bharti; Richa,; Sadadiwala, Shikha; Singh, Manimukta (Journal of Nepal Paediatric Society, 2022)
Tuberculosis is a serious public health issue in developing countries. Hypercalcemia, though reported in granulomatous disease, is mild and asymptomatic in tuberculosis. A 16 year old girl female presented with significant weight loss, loss of appetite and on examination hepatosplenomegaly. Ultrasound abdomen (USG) showed mesenteric and retroperitoneal lymphadenopathy with hepatosplenomegaly with mild ascites. We report an unusual case of hypercalcemia with renal injury due to abdominal tuberculosis in an immunocompetent female.